Dissipation of Residues of Endosulfan From Mungbean under Arid Conditions - Singh, M P (Annals of Arid Zone, 2016)
Residues of endosulfan 0.05 and O.1% sprays were determined on leaves, pods and grains of mungbean crop (cv S-8) raised at Jodhpur during rainy seasons of 1985 and 1986. Initial deposits were 10.89Â· 11.17 and 15.71- 16.40 ppm on leaves and 1.26 - 2.34 and 1.88 - 2.79 ppm on pods, from the two concentrations, respectively. Residues diSSipated completely within 21 days on leaves and within 10 days on pods. Waiting period of 2 days was arrived for the pods for human consumption. Grains contracted no residues of endosulfan at harvest.